Pelaksanaan dalam Menghidupkan Kembali Isro’ Mi’roj di Desa Racek - hidayat, Muhammad wahyu; Hasan, Pahlawan; Faiz, Muhammad; Ainul Yakin, Moh Gusaai; Patoni, Alpan; Maulana, Agung; Gilang, Muhamad; Rohim, Muhammad (Najah: Journal of Research and Community Service, 2024)
Based on the study of most interpretive scholars, the event of Isra' Mi'raj is a very special and majestic event because at the beginning of the verse Allah says starting with the word "Subhana" which means "Most Holy" which is not found in the 113 other Surahs in the Al-Qur'an. an. Therefore, it is clear that this most powerful event can represent proof of Allah's love and love for His beloved servant of the Prophet Muhammad SAW as the khatamin Nabiyyin and the climax of all the Shari'ah of Allah which was entrusted to the Prophet Muhammad SAW, prayer occupies a strategic and main position, because in the afterlife the first thing that will be questioned before other commands is prayer. Allah SWT firmly states in verse 1 of Surah al-Isra' about His power through His servant Muhammad with this mi'raj event, to show signs of His greatness by traveling a third of the night from the Grand Mosque in Makkah to the Aqsa Mosque in Palestine at a tremendous speed beyond the reach of human thought at that time. Plus the mi'raj trip from the Aqsa mosque to Sidratil Muntaha to receive prayer orders and at that time the Angel Gabriel was unable to meet Allah SWT directly and the Prophet Muhammad SAW himself was able to face RABB al-Alamin. Keywords: isra’ mi’raj